Instagram dalam Meningkatkan Penguasaan Kosakata Bahasa Jerman - Muhammad Wardiham Anwar; Laelah Azizah; Abdul Kasim Achmad (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This research is a True Experiment (Pre-test Post-test Control Group Design) study which aims to find out data and information on the effectiveness of Instagram media in increasing the German vocabulary of class XI students at SMA. The population of this study were students of class XI IPA SMA Negeri 8 Makassar, totaling 133 students from four classes. The sample in this study was selected randomly (random sampling), namely students in class XI IPA 5 as the experimental class, totaling 28 students, and class XI IPS 6 as the control class, totaling 28 students. The average (mean) value of the experimental class during the pre-test was 51.39 and the post-test was 87.46. Research data were analyzed using the t-test (Independent Sample t-test). The results of the data analysis showed that tcount 3.337 > ttable 2.004 at a significant level of 0.05. These results indicate that Instagram media is effective in increasing the German vocabulary of class XI students of SMA Negeri 8 Makassar.Keywords: Effektivnesss, Instagram, Vocabulary, German